Synergy of Dynamic Capability and Innovation: A New Model for Strengtheningclinic Performance Through Entrepreneurial Leadership - Nurcahyo UK, Chandra; Pusparini, Elok Savitri (Green Publisher Indonesia, 2025)
This study aims to analyze the impact of entrepreneurial leadership on clinical performance, by highlighting the role of Dynamic Capability and innovation capability. In the face of increasingly competitive competition in the health sector, clinics are expected to be able to adapt to changes and create relevant innovations to maintain optimal performance. This study uses a quantitative approach with a survey of clinic owners or leaders in Indonesia. The population in this study is the owner or leader of the Clinic in Indonesia, the sample determination was carried out by purposive sampling technique so that as many as 385 respondents were obtained. Research data was collected directly through an online questionnaire. Further research data was analyzed statistically using the partial least square method. The results of the study show that (1) entrepreneurial leadership directly contributes significantly to improving clinical performance, (2) Dynamic Capability acts as a mediator in the relationship between entrepreneurial leadership and clinical performance, (3) Innovation capability also functions as an important mediator, entrepreneurial leadership encourages the creation of new ideas and the implementation of innovation, which in turn contributes to the achievement of performance better clinics, (4) The combination of Dynamic Capability and innovation shows a synergistic effect in strengthening the relationship between entrepreneurial leadership and clinical performance. These findings underscore the importance of entrepreneurial leadership in encouraging sustainable adaptability and innovation in the health sector. The originality of this research lies in exploration of the relationship between entrepreneurial leadership, Dynamic Capability, innovation capability, and organizational performance.